SENTINEL 2 bands and reflectance of rock exposures in the Mourne Mountains, NI - Paul Slezak; Patrick O extquotesingleSullivan; Robbie Ramsay; Michael Stock; Ben Field; Andrea Fagan (PANGAEA, 2023)
The Hyperspectral Analysis of the Mourne Mountains (HAMM) project was undertaken from 2020-2022 in Northern Ireland to integrate spectral, geochemical, and remote sensing data from an exposed, non-arid setting. Mourne Mountain Complex (MMC) samples were obtained by donation from the Geological Survey of Northern Ireland (GSNI) and the Sedgwick Museum (University of Cambridge) as well as from the field by the authors. Samples represent the 5 primary granite types (G1, G2, G3, G4, G5), other minor rock types, and alteration styles. Some sample donations were historic and exact locations unspecified. Their reported coordinates are best estimates from historic literature and projections to surface (see notes in the datasets). Remote sensing spectra data (Level 2A–below atmosphere) was obtained from the European Space Agency extquotesingles (ESA) SENTINEL-2 satellite. Data and imagery were acquired from the ESA extquotesingles Copernicus Open Access Hub (ESA Copernicus 2022) and was processed using ENVI 5.6 and FLAASH module from L3Harris at University College Dublin. A recent image from August 2022 was chosen as there was little to no cloud cover over the MMC. The spectral data was extracted from the rocks exposed at surface as well as nearby vegetated, representing the major granite types from this study.